Desempenho de trator em função da velocidade e da pressão de inflação dos pneus da semeadora - Furlani, Carlos Eduardo Angeli [UNESP]; Cortez, Jorge Wilson; de Toledo, Anderson [UNESP]; da Silva, Rouverson Pereira [UNESP]; Grotta, Danilo Cesar Checchio; dos Reis, Gustavo Naves (FapUNIFESP (SciELO), 2010)
The performance of agricultural tractors under field conditions results from the interaction between tire and wheel affected by displacement speed. This work was developed to assess the performance of an agricultural tractor under different seeder's tire inflation pressure (518; 483 and 414kPa) and in two different gears providing speeds of 3.0 and 6.0km h-1. The experiment was performed at Jaboticabal Campus of São Paulo State University (UNESP). The experimental design used was entirely randomized in a 2-factor factorial design (3×2) with four replications. The draft force was influenced by the gear as well as by the required power; however, tire inflation pressure in the seeder did not change these parameters. Also, fuel consumption was influenced only by the tractor gear. Energy consumption was greater as speed increased, caused by gear shifting. The displacement speed was greater for the 518kPa pressure due to a lesser slippage in the seeder under this pressure. Tractor slippage did not change.
Tractor perfomance as a function of speed and seeder's tire inflation pressure
Keywords: Fuel consumption; No-tillage system; Slippage